Quality of rail passenger experience: the direct and spillover effects of crowding on individual well-being and organisational behaviour - Mohd Mahudin, Nor Diana (2012)
The challenge of rail passenger crowding has not been fully addressed in the scientific literature. This thesis describes a research work aimed at (1) investigating the relationships among the different psychological components of crowding and their effects on commuters’ experience of stress and feelings of exhaustion, and (2) exploring how the effects of rail passenger crowding can spill over to the individual’s broader work and life. To achieve these aims, an operational model is built that is consistent with the framework of Cox et al.’s (2006) model of crowding, stress, health, and safety, and is tested in a two-phase study. While Phase One of the research qualitatively explored the perceptions of rail passenger crowding and other associated issues among key stakeholder institutions (N = 5), Phase Two quantitatively examined the effects of rail passenger crowding on commuters’ individual well-being and their organisational behaviours (N = 525). The results of Phase One demonstrate that passenger crowding is perceived only as a minor problem compared to capacity, infrastructure, and service quality issues among the key stakeholders. On the other hand, the results of Phase Two reveal that crowding is indeed stressful for the commuters and has the potential to spill over to other aspects of their life and work. Using structural equation modelling techniques, the results show first the relationships among passengers’ evaluation of the psychosocial aspects of the crowded situation and of its ambient environment as well as their affective reactions to it, and the relationships among these psychological components of crowding and passenger density. Second, they demonstrate that the different psychological components of crowding together with rated passenger density are combinatorially predictive of commuters’ stress and feelings of exhaustion. Third, while the effects of crowding on feelings of exhaustion disappeared after controlling for demographic factors and individual differences in commuting experience, its effects on the experience of stress remained significant, further highlighting the negative consequences of rail passenger crowding. Fourth, the results reveal different patterns of spillover effects for passenger stress, particularly on commuters’ reports of somatic symptoms of ill health, their propensity for lateness and absenteeism at work, and intention to quit, but not in terms of their job or life satisfaction. The implications of these findings are discussed in terms of the existing literature and the operational framework set out at the beginning of the research work, which could lend support for future crowding research and management.